(untitled) (Libellarium: journal for research in the field of information and related sciences, 2026)
Purpose. Episciences is a platform for publishing overlay diamond open access scientific journals. It hosts and supports 43 overlay journals from several disciplines—mainly mathematics, informatics, applied mathematics, social sciences, and humanities—and, for this purpose, utilises open science infrastructures. Approach. The content of the publications is hosted on open repositories (such as HAL, arXiv, Zenodo, bioRxiv, and medRxiv), data repositories for datasets and Software Heritage for software. This allows Episciences to benefit from the FAIR principles supported by these infrastructures while also adding value and services. The platform offers a complete publishing solution for researchers, enabling them to peer-review and publish articles, datasets, and software. All these components may also be linked to each other to promote the FAIR principles and the reproducibility of science. Findings. Relying on existing infrastructures enables cost-efficient publishing. Led by academics, the platform is supported by French academic funding from the Ministry of Higher Education and Research, CNRS, Inria, and INRAE. Originality. The platform engages with scientific communities, through scientific committees. It provides solutions for copy-editing, communication, and advice on the best practices in open science publishing. Episciences is also open to new projects and collaborations at both European and international levels. The platform is available on the OpenAIRE catalogue of services and the EOSC marketplace. Relying on open infrastructures, the overlay model, and a dedicated support and editorial team, Episciences increases the transparency of the editorial workflow and enables researchers to regain control of their publishing methods and processes.